Study guides

Q: What is the square root of 4x² over 3y?

Write your answer...

Submit

Related questions

(4x + 3y)(4x + 3y) or (4x + 3y)2

We use the property of square roots that says the square root of (ab)=square root (a) multiplied by square root of b So square root (4x)=square root (4) mutiplies by square root of x =2(square root (x)) 2sqrt(x)

4x to the sixth can be expanded to (4x * 4x * 4x)(4x * 4x * 4x) or (4x to the third)(4x to the third) the square root of the above would be 4x to the third

square root of 4x is 2 times square root of x, so answer is square root of x times 3 since it is 2 square roots of x plus one of them

If you square an expression and then take the square root, the squaring and the square root cancel one another, EXCEPT that the sign will be positive. Thus, if you square 16x, and then take the square root, the answer can be 16x or -16x, depending on whether "x" is positive or negative. Or if you only square x, and then take the square root of the entire expression, it would be 4x or -4x (once again, depending on whether "x" is positive or negative).

3y = 4x + 9 -4x + 3y = 9 is the standard form

6x+3y+5z-4x+4z-5y=

-4x + 3y = 9

3y=4x+9.....-4xAnswer: 4x-3y=9

The square root of 4x^2 is solved by first doing the square root of 4. This is plus or minus two - because -2 x -2=4. The square root of x^2 is x. So the answers are 2x or -2x. If your question was (4x)^2, then the answer would be 4x.

16x2 + 8x + 1 - 9y2 = (4x + 1)2 - (3y)2 which is a difference of two squares. = (4x + 1 + 3y)*(4x + 1 - 3y)

If you mean: 4x+3y = -1 and x-3y = -34 then x = -7 and y = 9

4x + 3y = 8x + y so 3y - y = 8x - 4x ie 2y = 4x so y = 2x

4x+3y = 12 3y = -4x+12 y = -4/3x+4

2x + 3y + 4x + 9y = 2x + 4x + 3y + 9y = 6x + 12y which can be simplified to 6(x + 2y)

4x+3y = 6 3y = -4x+6 y = -4/3x+2 in slope intercept form

If you mean: 4*square root of x2 then it is 4x

The solution of 4x plus 3y -9 and x -3 is; 5x+3y-3.

8x-3y=6-4x gives 12x-3y=6 which in standard form is y=-2+4x

If you mean: -8y-(x-4x)+3y then it is 3x-5y simplified

If: -4x+3y = 1 Then: 3y = 4x+1 And: y = 4/3x+1/3 which is now in slope-intercept form

3y2 - 2y + 6xy - 4x = y(3y - 2) + 2x(3y - 2) = (y + 2x)*(3y - 2)

4x + 12y = 4(x + 3y)

4x + 3y=9 x=0 y=3

4x+3y = 3 3y = -4x+3 y = -4/3x+1 in slope intercept form